Human Resource Management Perspective on Management of Change in State-Owned Enterprises - Arvid Muzanenhamo (CV. Literasi Indonesia, 2023)
The purpose of this study is to identify the role of human resource management in the change processes of state-owned enterprises and its effectiveness in the management of organizational change. This paper is a study of the role of human resource professionals in the internal change processes of state-owned enterprises. Qualitative research was used, and semi-structured interviews were administered to obtain data from human resource practitioners and departmental supervisors in a South African state-owned enterprise. Human Resource professionals are the custodian of change and employee champions in organizations. Their input in change processes is vital in maintaining employee levels of commitment to the organization. Human Resource Management's role in organizational change involves employee counseling, motivation, communication, and designing exit packages. If these roles are not properly executed, the organization may experience difficulties such as employee stress, low morale, and high labor turnover to mention just a few. The study revealed that lack of business partner roles, fear and control by the executives, and lack of communication from the top management are the challenges facing human resource professionals during internal change processes. The study provides insights for top management in state-owned enterprises on the role of human resource management in organizational change processes. The discussion provided in this paper would strengthen the body of knowledge on the role of Human Resource Management in the management of change particularly in state-owned enterprises.